Pro JavaScript design patterns - Harmes, Ross (Expert's voice in Web development., 2008)
As a web developer, you'll already know that JavaScript is a powerful language, allowing you to add an impressive array of dynamic functionality to otherwise static web sites. But there is more power waiting to be unlocked-JavaScript is capable of full object-oriented capabilities, and by applying object-oriented principles, best practices, and design patterns to your code, you can make it more powerful, more efficient, and easier to work with alone or as part of a team. With Pro JavaScript Design Patterns, you'll start with the basics of object-oriented programming in JavaScript applicable to design patterns, including making JavaScript more expressive, inheritance, encapsulation, information hiding, and more. With that covered, you can kick-start your JavaScript development in the second part of the book, where you'll find detail on how to implement and take advantage of several design patterns in JavaScript, including composites, decorators, façades, adapters, and many more. Each chapter is packed with real-world examples of how the design patterns are best used and expert advice on writing better code, as well as what to watch out for. Along the way you'll discover how to create your own libraries and APIs for even more efficient coding. Master the basics of object-oriented programming in JavaScript, as they apply to design patterns Apply design patterns to your kick-start your JavaScript development Work through several real-world examples.